2008
DOI: 10.1002/ejoc.200800028
|View full text |Cite
|
Sign up to set email alerts
|

Three Phase Microemulsion/Sol–Gel System for Aqueous C–C Coupling of Hydrophobic Substrates

Abstract: Heck, Stille, Suzuki and three‐component coupling reactions with hydrophobic substrates have been carried out in water. The substrates are initially transformed by a general procedure into a microemulsion, which consists of nearly 90 % water with the aid of sodium dodecyl sulfate and either PrOH or BuOH. The surfactant carries the molecules of the substrates to Pd(OAc)2 entrapped within a hydrophobicitized silica sol–gel matrix where the coupling between the substrates is assumed to take place. The products ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…[4] A typical TEM image is shown in Figure 1A. Dark contrast of heavy dense crystalline Pd nanoparticles is seen on the image.…”
Section: Resultsmentioning
confidence: 94%
“…[4] A typical TEM image is shown in Figure 1A. Dark contrast of heavy dense crystalline Pd nanoparticles is seen on the image.…”
Section: Resultsmentioning
confidence: 94%
“…After removal of the imprint the matrices were used in the Heck coupling reactions that led to the corresponding mono-and dimethylated stilbenes. As noted in our previous paper, [5] both methylated bromobenzenes and methylated styrenes react much slower than the unsubstituted substrates. Nevertheless, with extension of the reaction time, substantial amounts of the cisoriented stilbenes have been formed (see Table 1), and here too the immobilized catalyst could be recovered and recycled after completion of the couplings (4 runs were investigated in each case).…”
mentioning
confidence: 83%
“…The specific reaction with which we demonstrate this approach is the palladium acetate-catalyzed Heck coupling [3,4] of a bromoarene and a styrene derivative in an aqueous microemulsion. [5] This reaction has led to hardly any cis products when carried out in solution, [3,4] and to no cis products at all under heterogeneous sol-gel conditions. [5] We found that we could force this reaction to yield considerable amounts of cis-stilbenes -typically cis:trans ratios of 1:1, and up to 8.5:1 -by imprinting the matrix within which the catalyst is embedded with cis-stilbenes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Bereits in einem früheren Beitrag wurden Tensidsysteme als vielseitige Medien in einer HeckReaktion mit einem Palladium-Heterogenkatalysator beschrieben. [11] Da [12] in Gegenwart von Wasser erleichtert wird. Wie in Tabelle 1, Nr.…”
unclassified